Atomic spectrometry update: review of advances in the analysis of metals, chemicals and materials. Issue 11 (20th September 2017) - Carter, Simon; Fisher, Andy; Gibson, Bridget; Marshall, John; Russell, Ben; Whiteside, Ian
Abstract : This review covers advances in the analysis of advanced materials, metals, fuels and lubricants, nanostructures, ceramics, refractories, organic and inorganic chemicals, catalysts and nuclear materials by a range of techniques including X-ray, ICP, LIBS, mass spectrometry, synchrotron-based techniques, plus non-destructive and ablation surface techniques. Abstract : This ASU review focuses on developments in applications of atomic spectrometry to the characterisation of metals, chemicals and materials. It is difficult to identify research trends solely from an annual review of the literature, but a certain perspective can be obtained from examining the developments described in recent years in this ASU review series. It is, for example, evident that there has been a decline in truly novel applications for the analysis of chemicals, perhaps indicative of the fact that, for most sample types, there is now an abundance of methods available in the literature. Those papers that have appeared in the year under review have either focused on specific problems not yet fully addressed ( e.g. determination of Si in gasoline) or on incremental development of well-established approaches to sample preparation or measurement. Nevertheless, there has been a very noticeable increase in activity in relation to publication of methods for the characterisation of pharmaceuticals. This is directly linked to changes in the US Pharmacopeia requirements for registration of pharmaceuticals for human use that require assessments to be made for trace element content. Laser-induced breakdown spectrometry is becoming widely employed for applications involving the characterisation of a wide variety of metals, materials and other solid sample types. Efforts are being made to overcome the perceived weaknesses of the technique, such as lack of sensitivity, elemental fractionation, accuracy and/or precision. Advances have been made, for example, using dual-pulse lasers to improve sensitivity, or by employing chemometrics methods with full spectrum data to improve the robustness of calibration. Many of these reported LIBS developments draw from, and have relevance for, applications involving LA-ICP-MS, which continues to be a popular means of generating highly sensitive lateral and depth profiling and bulk compositional information for a wide range of materials and solids. The use of field portable instrumentation for in situ analysis continues grow, with LIBS and XRF techniques amongst those most frequently cited. The development of such instrumentation has had a substantial impact in the examination of cultural heritage artefacts, especially in relation to paintings, wall murals and other objects of unique historical value. The latter area of application has also seen continued use of combinations of surface (SIMS, XPS, SEM-EDS, PIXE, GD and laser ablation methods) and bulk (ICP-OES, ICP-MS, AAS, XRF) analysis techniques to reveal details of objects that would not otherwise be identified (for example preparatory sketches hidden under original works of art or materials provenance). This trend towards using a multi-technique based approach has also been apparent in the characterisation of multi-layer or heterogeneous organic and inorganic materials and metals. Finally, methods for the analysis of nanoparticles and nanostructures have been reported, based primarily on single particle (SP)-ICP-MS and flow field flow fractionation (A4F). The investigation of methods of drift correction, the use of flow injection and isotope dilution methodologies in combination with SP-ICP-MS are indicative of the further development of this field.